Does drainage or resection predict subsequent interventions and long-term quality of life in patients with Grade IV pancreatic injuries: A population-based analysis. Issue 4 (October 2021) - Ball, Chad G.; Biffl, Walter L.; Vogt, Kelly; Hameed, S. Morad; Parry, Neil G.; Kirkpatrick, Andrew W.; Kaminsky, Matthew
Abstract : BACKGROUND: Clinical equipoise remains significant for the treatment of Grade IV pancreatic injuries in stable patients (i.e., drainage vs. resection). The literature is poor in regards to experience, confirmed main pancreatic ductal injury, nuanced multidisciplinary treatment, and long-term patient quality of life (QOL). The primary aim was to evaluate the management and outcomes (including long-term QOL) associated with Grade IV pancreatic injuries. METHODS: All severely injured adult patients with pancreatic trauma (1995–2020) were evaluated (Grade IV injuries compared). Concordance of perioperative imaging, intraoperative exploration, and pathological reporting with a main pancreatic ductal injury was required. Patients with resection of Grade IV injuries were compared with drainage alone. Long-term QOL was evaluated (Standard Short Form-36). RESULTS: Of 475 pancreatic injuries, 36(8%) were confirmed as Grade IV. Twenty-four (67%) underwent a pancreatic resection (29% pancreatoduodenectomy; 71% extended distal pancreatectomy [EDP]). Patient, injury and procedure demographics were similar between resection and drainage groups ( p > 0.05). Pancreas-specific complications in the drainage group included 92% pancreatic leaks, 8% pseudocyst, and 8% walled-off pancreatic necrosis. Among patients with controlled pancreatic fistulas beyond 90 days, 67% required subsequent pancreatic operations (fistulo-jejunostomy or EDP). Among patients whose fistulas closed, 75% suffered from recurrent pancreatitis (67% eventually undergoing a Frey or EDP). All patients in the resection group had fistula closure by 64 days after injury. The median number of pancreas-related health care encounters following discharge was higher in the drainage group (9 vs. 5; p = 0.012). Long-term (median follow-up = 9 years) total QOL, mental and physical health scores were higher in the initial resection group ( p = 0.031, 0.022 and 0.017 respectively). CONCLUSION: The immediate, intermediate and long-term experiences for patients who sustain Grade IV pancreatic injuries indicate that resection is the preferred option, when possible. The majority of drainage patients will require additional, delayed pancreas-targeted surgical interventions and report poorer long-term QOL. LEVEL OF EVIDENCE: Epidemiology/Prognostic, Level III.